Diseño de un plan de emergencia para el edificio l del campus Edison Riera de la Universidad Nacional de Chimborazo - Franklin Vicente, Ramos Flor (2022)
ABSTRACT: The objective of this research was to design an emergency plan for building L of the Édison Riera campus of the National University of Chimborazo based on current legal regulations that contribute to compliance with accident prevention and mitigation standards in the event of an accident. Occur an event of natural or anthropic origin. For the identification of risks, information was collected through on-site inspection, observing each of the spaces and resources available in the different environments of the building. Later they were evaluated by applying the FEMA, MESERI method, and matrix of vulnerability for institutions. The population under study was 1,805 users, which is the maximum capacity of the building. The results obtained in this investigation determined that the threats to which building L is exposed are: earthquakes, floods, epidemics and plagues, fire, explosion, gas leaks, assault theft, and civil disorder. The FEMA 154 analysis determined a low vulnerability, which indicates that the building does not need to reinforce its structure. According to the MESERI fire assessment, a value of 5.44 was obtained, corresponding to medium risk. The vulnerability analysis for institutions showed a medium value for human and environmental factors, property resources, systems, and processes. With the information generated, the emergency plan was designed, serving as an adequate planning and organization tool to improve the response capacity in an emergency to protect the well-being of people, property, and the environment.